Resonant and a new disturbance-observer combined control for off-grid voltage source inverter - Marco di Benedetto; Mi Tang; Alessandro Lidozzi; Luca Solero; Andrea Formentini; Pericle Zanchetta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents a new control strategy based on the combination between the resonant controller and the disturbance-observer (RSCDO) for stand-alone four-leg Voltage Source Inverter (VSI). The aim of the new controller is to regulate the inverter output voltage, reducing as much as possible the voltage Total Harmonic Distortion (THDv) in every load condition. The resonant controller allows to adjust the output voltage fundamental harmonic, whereas the disturbance observer is designed for compensating output voltage harmonics when non-linear loads have to be fed. The proposed control strategy has been tested using a 40 kVA three-phase 4-leg VSI and a dedicated control board, which uses the National Instruments System-on-Module sbRIO-9651. Experimental results demonstrate good behavior of the RSCDO controller to reject the disturbance in the output voltage, as well as a good dynamic response.